2023
DOI: 10.3390/jimaging9080151
|View full text |Cite
|
Sign up to set email alerts
|

Fast Compressed Sensing of 3D Radial T1 Mapping with Different Sparse and Low-Rank Models

Abstract: Knowledge of the relative performance of the well-known sparse and low-rank compressed sensing models with 3D radial quantitative magnetic resonance imaging acquisitions is limited. We use 3D radial T1 relaxation time mapping data to compare the total variation, low-rank, and Huber penalty function approaches to regularization to provide insights into the relative performance of these image reconstruction models. Simulation and ex vivo specimen data were used to determine the best compressed sensing model as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Previous work has accelerated the VFA protocol using sparse sampling techniques with compressed-sensing reconstruction. 29,[58][59][60][61] It was shown that a 1-mm isotropic multi-echo MT sat protocol using a compressed-sensing VFA protocol could be acquired in 15:40 (min:s) using a 4-times undersampling and in 10:30 with 6-times undersampling factor. 29 This produced high-quality quantitative maps in which metric variance increased with acceleration factor, with minimal acceleration-induced bias.…”
Section: Csmp2rage Shortens Mt Sat Acquisition Timesmentioning
confidence: 99%
“…Previous work has accelerated the VFA protocol using sparse sampling techniques with compressed-sensing reconstruction. 29,[58][59][60][61] It was shown that a 1-mm isotropic multi-echo MT sat protocol using a compressed-sensing VFA protocol could be acquired in 15:40 (min:s) using a 4-times undersampling and in 10:30 with 6-times undersampling factor. 29 This produced high-quality quantitative maps in which metric variance increased with acceleration factor, with minimal acceleration-induced bias.…”
Section: Csmp2rage Shortens Mt Sat Acquisition Timesmentioning
confidence: 99%